Metabolic Engineering of Microorganisms for the Production of Flavonoids - Sheng, Huakang; Sun, Xinxiao; Yan, Yajun; Yuan, Qipeng; Wang, Jia; Shen, Xiaolin (Frontiers in Bioengineering and Biotechnology, 2020)
Flavonoids are a class of secondary metabolites found in plant and fungus. They have been widely used in food, pharmaceutical, and nutraceutical industries owing to their significant biological activities, such as antiaging, antioxidant, anti-inflammatory, and anticancer. However, the traditional approaches for the production of flavonoids including chemical synthesis and plant extraction involved hazardous materials and complicated processes and also suffered from low product titer and yield. Microbial synthesis of flavonoids from renewable biomass such as glucose and xylose has been considered as a sustainable and environmentally friendly method for large-scale production of flavonoids. Recently, construction of microbial cell factories for efficient biosynthesis of flavonoids has gained much attention. In this article, we summarize the recent advances in microbial synthesis of flavonoids including flavanones, flavones, isoflavones, flavonols, flavanols, and anthocyanins. We put emphasis on developing pathway construction and optimization strategies to biosynthesize flavonoids and to improve their titer and yield. Then, we discuss the current challenges and future perspectives on successful strain development for large-scale production of flavonoids in an industrial level.